PERANAN DIREKTORAT PENGAMANAN OBJEK VITAL DALAM PENGAMANAN OBJEK WISATA TERHADAP TINDAK PIDANA PENCURIAN DI KOTA PEKANBARU - Kurniawan, Yogi; Indra, Mexsasai; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The high level of crime in the theft of the tourist attractions in the city of Pekanbaru causing public anxiety and fear, so reluctant to visit tourist attractions in the city of Pekanbaru. Some causes of this discomfort role Vital Security Object (PAM OBVIT) increasingly vital. Protect and make the tourists feel comfortable and safe are the main tasks that must be performed by members of the Vital Security Object (PAM OBVIT). Based on this understanding, then writing this essay to formulate three formulation of the problem, namely: first, how the role of the security directorate in securing vital objects attraction to the criminal offense of theft in Pekanbaru City? Second, whether the security directorate inhibiting factor in securing vital objects attraction of the offenses of theft in Pekanbaru City? Third, if the efforts made object security directorate vital in overcoming obstacles Attraction security against criminal acts of theft in the city of Pekanbaru?Keywords: Role - DirPamObvit – Pekanbaru